Residential satisfaction and the propensity to stay : an analysis of potential movers from low cost house - Syahrizan, bin Junaini (Universiti Malaysia Sarawak (UNIMAS), 2011)
This research is designed to study potential factors contributing to satisfaction and dissatisfaction among low cost house owners residing in Kuching, Sarawak. This study also focuses on reasons for low cost house owner to continue staying at their property and also potential pulling factors to draw them to move out and owning other propert~ The findings show that factors can be grouped into dwelling unit factors, neigbourhood factors and community factors respectively. The findings endow potential recommendations to the Government, Housing Development Authorities, developers and local authorities to provide better services in increasing satisfaction among low cost house owners in the future thus increasing their propensity to continue staying at low cost house.